Traditional Land Practice and Forest Conservation: Case Study of The Manggarai Tribe in Ruteng Mountains, Indonesia (Komunitas, 2016)
Conservation of mountain forests in the tropics will be successful if the interests of local communities to be considered in the management. Indigenous system of forest management for the sustainable use is  the most appropriate for better understand to the environmental conditions. This study aimed to analyze the traditional land management by Manggarai communities and integrate them into forest conservation. This research is a qualitative ethnographic approach. Qualitative data in 2014 obtained through observation, interviews, data from relevant agencies and related literature. The results showed that the Manggarai community has been practicing traditional land management and sustainable use zoning system. Indigenous land use practice is done by considering the sustainability and preventing land degradation.